(untitled) (La U Investiga, 2022)
The uterus of couvaliere, also called uteroplacental apoplexy, is a complication of premature placental abruption because there is a retroplacental hematoma due to the rupture of spiral arteries that causes blood to penetrate the myometrium and parametrium, even in very rare cases, to the peritoneal cavity. allowing the separation of the placenta with the uterus and thus infiltrating to the serosa of the uterus, all this is macroscopically evidenced as a bluish-purple uterus. As a result, the musculature of the myometrium cannot contract properly and therefore causes postpartum bleeding, due to uterine atony that transforms from hypertension to hypotension static. It occurs in 0.4-1% of pregnancies, the decisive factor in the pathophysiology is hemorrhage, in the placental decidual interface, which causes stillbirth, maternal hypovolemic shock, disseminated intravascular coagulation and renal failure.